”Where is your nose?” : developing body awareness skills among children with autism using a humanoid robot - Costa, Sandra (2013)
This article describes an exploratory study in which children with autism interact with KASPAR, a humanoid robot, equipped with tactile sensors able to distinguish a gentle from a harsh touch, and to respond accordingly. The study investigated a novel scenario for robot-assisted play, namely to increase body awareness with tasks that taught the children about the identification of human body parts. Based on our analysis of the childrens behaviours while interacting with KASPAR, our results show that the children started looking for a longer period of time to the experimenter, and a lot of interest in touching the robot was observed. They also show that the robot can be considered as a tool for prolonging the attention span of the children, being a social mediator during the interaction between the child and the experimenter. The results are primarily based on the analysis of video data of the interaction. Overall, this first study into teaching children with autism about body parts using a humanoid robot highlighted issues of scenario development, data collection and data analysis that will inform future studies.